A critique of America: Occidentalism in Umar Kayam’s Cold War literature Seribu Kunang-Kunang di Manhattan - Muhammad Taufiqurrohman; Sudibyo Sudibyo; Fadlil Munawwar Manshur (Universitas Muhammadiyah Malang, 2026)
Cold War literary studies remain dominated by Western perspectives, particularly narratives from the United States and the Soviet Union, resulting in the marginalization of literary experiences and criticism from Third World countries. Indonesian literary works that represent America as an object of critique have seldom been read as integral to global Cold War literary discourse. This research aims to uncover and explain criticisms of the United States in Umar Kayam's short story collection Seribu Kunang-Kunang di Manhattan within the context of Cold War Literature, using Indonesia’s perspective as part of the Third World. This study employs a qualitative-descriptive approach within a postcolonial framework, combining the concept of Occidentalism with an intersectional analysis of race, class, and gender. The analytical method used is a wide, close, and deep reading approach that integrates textual analysis and historical documents. The research data include primary textual units from short stories, as well as secondary data, including historical, and relevant academic literature. The results show that Kayam delivers an ideological critique of America by portraying it as a dark and ambiguous space, with a working-class society that is vulnerable and apolitical, and patriarchal gender relations, thereby dismantling the myth of America as a symbol of progress and universal freedom. This research concludes that Indonesian literature serves as a legitimate medium for cultural and ideological critique of Western hegemony, while also affirming Indonesia’s active position in global Cold War literary discourse.